Analysis of Pap smears in a cytopathology lab of a teaching hospital - Baral, Reetu Sharma (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: This study was done to find out age wise distribution pattern, cellular abnormality and adequacy of Pap smears. Methods: A retrospective study of 470 Pap smears based on laboratory record was done from September 2019 to April 2020 at B and C Medical College Teaching Hospital, Birtamod, Jhapa, Nepal. Descriptive analysis performed using MS Excel and SPSS 16. Results: Out of 470 analyzable data 2.55% had abnormal cytology, all high-grade lesions were in 30-49 age group and 0.21% were detected as carcinoma. Mean age of women was 39.2±10.5 years. Age distribution follows the normal Gaussian curve. Age group of 30-60 years consists of four-fifth (75.5%, n=355) and Two-third of cases (66.4%, n=312) were of age group 30-49 years. Conclusions: Pap samples were normally distributed by age. Test requisition forms lack adequate clinical information. Even the inadequately sampled Pap smears were satisfactory for evaluation. Keywords: cancer, cervix, intraepithelial lesion, Pap smear, screening